THE WORK OF THE SCHOOL MEDIATION SERVICE - Bozhko , Inna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article discusses the concept and algorithm of the school mediation service.